Culturally Responsive Comics: Developing South Sumatra-Based Media to Foster Cultural Understanding in Primary Education - Yani, Fitri Dwi; Kawuryan, Sekar Purbarini (Papanda Publisher, 2025)
This study explores the development and implementation of socio-cultural comics based on South Sumatran culture in elementary schools in Indonesia, focusing on their impact on student engagement and cultural understanding. The comics were designed to introduce local traditions, values, and customs through visually engaging narratives, enhancing students' emotional and cognitive connection to their cultural heritage. Significant improvements were observed in student participation during cultural discussions, deeper understanding of traditional practices, and greater pride in local identity. A qualitative approach with a phenomenological research design was employed, involving six teachers and twenty-four students in grades IV and V, alongside classroom observations. The participants came from diverse socio-cultural backgrounds in South Sumatra. The findings reveal that socio-cultural comics significantly increase student engagement, motivation, and understanding of cultural values. However, challenges such as limited availability of learning media, variation in students’ cultural exposure, and the need for teacher training in media integration were identified. The study recommends developing teacher capacity in integrating comics into the curriculum, contextualizing comic content to reflect local student experiences, and increasing the accessibility of comics in schools, particularly in rural areas**. This research contributes valuable insights into the role of culturally responsive learning media in strengthening cultural understanding and character education among young learners. Future research could examine the effectiveness of digital-based comics, their long-term impact on students’ cultural identity development, and their scalability across different regions in Indonesia.